De la Sorbonne à l’Asie. Routes orientalistes d'Ena Bazin-Foucher (1889-1952) - Annick Fenet (Genre & Histoire)
This article follows the life of  Eugénie Bazin-Foucher, wife of the French indianist Alfred Foucher (1865-1952): her higher education in Paris ; her encounter with her future husband,  a teacher at the Sorbonne University ; their marriage in Ceylan in 1919 ; their eight years of travel (until 1926) in archaeological and scientific missions in India, Persia, Afghanistan and the Far East ;  and finally their Parisian life until their death. The couple's archives allow one to reconstruct Eugénie's participation in the work of her husband as well as shedding light on  her personality, her scientific aspirations and her originality in the intellectual world of the Interwar period.